Literature Review : Decentralization Analysis In Improving Managerial Performance - Trisnaningsih, Sri; Ariadi , Deni (Journal Research of Social Science, Economics, and Management, 2022)
In the era of the digital economy 4.0 competition in the world of technology and information is increasing, today companies are required to maintain human resources in order to decentralize and evaluate performance in a contiunity manner in order to make the right decisions. In the study, the goal is to analyze more deeply about decentralization in improving manjerial performance. Researchers use the literature review approach, which is a systematic, explicit and reproducible method to identify, evaluate and synthesize the work of research results and the results of thoughts that have been produced by researchers and practitioners. The review literature aims to make an analysis and synthesis of existing knowledge related to the topic to be studied in order to find a blank space for the research to be carried out. The data source used by the author is in the form of secondary data, where the researcher uses 4 articles obtained from the google scholar database. The results of this study suggest that decentralization is useful for making a positive contribution to management performance, this is because decentralization is a process of delegation of responsibilities and authorities starting from upper level management to lower level management. Decentralization has a very important role for management because it is able to be considered to be able to help management in the right and efficient decision-making process, so that managers have the initiative to take action to solve problems that arise so that the decision making can be done quickly and precisely.